Post-Privatization Performance-Regulating Telecommunications in the U.K : Testing for Regulatory Capture - Dnes, Antony (World Bank, Washington, DC, 2012)
Privatized in 1984, British Telecommunications (BT) is the longest-standing privatized utility in the United Kingdom. Comparing BT's stock market returns over a long period with returns for a comparable sample of firms not affected by regulation, the author assesses whether the new telecommunications regulatory regime has been "captured" (unduly influenced) by consumer groups, BT, or BT's competitor. He concludes that some regulatory decisions have favored consumers, some have accommodated BT, and some have favored BT's competitor and that, overall, the regulatory regime has checked monopoly power.